Breakthyrough Windows Vista: Find Your Favourite Features and Discover the Possibilities
With this book discover the possibilities of what you can do with Windows Vista! Packed with information in manageable-sized projects, discover everything from how to set up your new operating system, access the Windows Vista Sidebar and customize it with the gadgets you use most; the media possibilities with Windows Vista; set up Media Center and watch and record live television; create, share, and organize your photos, music, and videos; be a director and make your own movies with Movie Maker!